Optimizing restaurant recommendations through sentiment analysis - Juha, Tasnia; Chowdhury, Shaira; Trina, Sultana Marium; Ami, Md Fardin Rahman; Hasme, Abu Obaida (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.